Learning Ecological Concepts in Secondary Schools of the Northeast of Spain - Meritxell Notari Llorens; Francisco Pardo Fabregat; Africa Martinez-Poveda; Manuel Jordan Vidal (MDPI AG, 2019)
Ecological concepts are not a recent matter; international organizations have already increased their efforts to provide better environmental education and ecological consciousness, although despite these efforts, a lack of attitudes and concepts were detected in the northeast of Spain. We evaluated the acquisition of concepts related to environmental education in the students as proposed by current legislation, as well as their relation to different parameters, such as geographical location, type of school, and gender. The result suggests that the students achieve a meaningful learning of the concepts proposed by legislation and that acquisition of this knowledge is related to gender and geographical location, but not to the type of secondary school.